Challenges faced by diagnostics companies from Tier 2 and Tier 3 cities during mergers and acquisition in India - Subhash Dagar, Rupesh (Digital Repository of Theses, 2025)
This study aims to assess the merger and acquisition, which is on a growing phase and is approached at a high level in a diagnostic Industry in India in tier 2 and tier 3 cities, as they want to capture markets with full speed but one rarely achieves their desired financial and strategic objectives. Over the last two decades based on my personal experience I believe 3 key major factors account for the dismal track record of merger and acquisition, including underestimating the multitude of integration issues and problems that arise due to cultural gaps, Integration failure and due diligence between both the parties. These dynamics have been found in tier 2 and tier 3 cities diagnostic players as they face a challenge of understanding the merger and acquisition process. Purpose: This dissertation is presented to provide input on the various models, mergers and acquisitions, which can be successfully concluded with minimum failure for tier 2 and tier 3 cities diagnostic player’s deals. Model will be based on considering existing mindset of smaller diagnostic players who understand the value of culture fit, integration and due diligence in the process of mergers and acquisitions. Design/methodology/approach: This qualitative study has been put forth based on the feedback received from various industry leaders like CEOs, COO and various functional departments associated with diagnostic industry. Entrepreneurs of small diagnostic player data were analyzed using a constant comparative method. The primary research method for this study is survey, modeling and case study. Findings: Culture of the organization, Lack of intelligence, transparency, trust factors of smaller diagnostic players from smaller towns, least importance given to documentation during mergers and acquisitions by both the parties resulted in merger and acquisition failure. Research limitations/implications: Given the method of this study, the findings are not intended for generalization to larger populations. Future research should address the need of smaller players to understand the finer aspects of the integration process, due diligence process and culture misfit whenever they go for mergers and acquisitions deals.